2019
DOI: 10.3389/fnagi.2019.00096
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea Improves Spatial Memory and Cognitive Plasticity in Mice and Has a Mild Effect on These Parameters in a Down Syndrome Mouse Model

Abstract: Down syndrome (DS), a genetic disorder caused by partial or complete triplication of chromosome 21, is the most common genetic cause of intellectual disability. DS mouse models and cell lines display defects in cellular adaptive stress responses including autophagy, unfolded protein response, and mitochondrial bioenergetics. We tested the ability of hydroxyurea (HU), an FDA-approved pharmacological agent that activates adaptive cellular stress response pathways, to improve the cognitive function of Ts65Dn mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…The forgetting of non-essential memory is an important component of learning and can be assessed by reversal water maze ( Nonaka et al, 2017 ; Brose et al, 2019 ), and previous study showed that female but not male APP/PS1 mice showed deficits in this paradigm ( Gallagher et al, 2013 ). Immediately following the 72 h probe trials of MWM, females (Eu (n=10), TcMAC21 (n=9)) were tested in RRWM that had the same spatial reference as MWM and consisted of two reversal sessions.…”
Section: Resultsmentioning
confidence: 99%
“…The forgetting of non-essential memory is an important component of learning and can be assessed by reversal water maze ( Nonaka et al, 2017 ; Brose et al, 2019 ), and previous study showed that female but not male APP/PS1 mice showed deficits in this paradigm ( Gallagher et al, 2013 ). Immediately following the 72 h probe trials of MWM, females (Eu (n=10), TcMAC21 (n=9)) were tested in RRWM that had the same spatial reference as MWM and consisted of two reversal sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxyurea (HU), a United States Food and Drug Administration-approved drug [1], is an inhibitor of ribonucleotide reductase commonly used to treat myeloproliferative disorders and sickle cell anemia [2]. In addition, HU is used as an anti-tumor drug to treat various malignancies [3].…”
Section: Introductionmentioning
confidence: 99%
“…People with DS have a high risk of developing early-onset dementia, and previous studies show that Ts65Dn mice lose the ability to acquire any spatial learning and memory in MWM at ~ 6-month-old [ 11 , 12 ]. To analyze the effects of forebrain hShh overexpression on early-onset severe cognitive impairment in Ts65Dn, we tested the forebrain-cohort in an MWM decorated with different spatial references at 7-month-old.…”
Section: Resultsmentioning
confidence: 99%